Sustainable international business model innovations for a globalizing circular economy: a review and synthesis, integrative framework, and opportunities for future research - Chabowski, Brian R.; Gabrielsson, Peter; Hult, G. Tomas M.; Morgeson, Forrest V. (Journal of International Business Studies, 2025)
Abstract The global imperative has increased in recent years for international firms to respond to major threats such as unintended environmental, social, and economic problems arising from ecological destruction, population growth, and economic activity. To respond to this confluence that has created an emerging existential crisis, we identify that a globalizing circular economy (CE) is required and subsequently define a new construct: sustainable international business model innovations. In doing so, we introduce circular inputs, sharing platforms, product as a service, product use extension, and resource recovery as business models that contain the potential to reply to these grand challenges. Based on CE principles, the innovations and designs introduced are contrasted with the traditional linear economic model and are presented as actionable standardization/adaptation alternatives for companies responding to differing informal and formal international institutions. Based on the theoretical underpinnings of the resource-based, dynamic capabilities, and international business model innovation perspectives, we introduce an integrative framework that is accompanied by a series of detailed research questions to provide future research opportunities for the domain. This conceptual approach holds that international resource design influences marketing capabilities adaptation which, in turn, impacts international performance and offers a foundation from which to build the literature.